2019
DOI: 10.3389/fimmu.2018.03118
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 1F Regulates M1-Polarization by Stimulating Intercellular Adhesion in Macrophages

Abstract: Intestinal macrophages are highly mobile cells with extraordinary plasticity and actively contribute to cytokine-mediated epithelial cell damage. The mechanisms triggering macrophage polarization into a proinflammatory phenotype are unknown. Here, we report that during inflammation macrophages enhance its intercellular adhesion properties in order to acquire a M1-phenotype. Using in vitro and in vivo models we demonstrate that intercellular adhesion is mediated by integrin-αVβ3 and relies in the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 89 publications
4
31
1
Order By: Relevance
“…In the pulmonary fibrosis model, the extracellular matrix via the α4β1 integrin leads to the activation of Rac2 and potentially regulates macrophage M2 differentiation (Joshi et al, 2017). In the colitis model, the Integrin αVβ3 polarized macrophages toward M1-type by promoting the overactivation of STAT1/3 downstream of the ILK/Akt/mTOR signaling pathway (Piedra-Quintero et al, 2019). In vitro environment of hydrogels containing RGD, with the presence of interleukin-4, integrin α2β1 may cause the polarization of macrophages to M2 through STAT6 and to M1 through IRF5 (Cha et al, 2017).…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…In the pulmonary fibrosis model, the extracellular matrix via the α4β1 integrin leads to the activation of Rac2 and potentially regulates macrophage M2 differentiation (Joshi et al, 2017). In the colitis model, the Integrin αVβ3 polarized macrophages toward M1-type by promoting the overactivation of STAT1/3 downstream of the ILK/Akt/mTOR signaling pathway (Piedra-Quintero et al, 2019). In vitro environment of hydrogels containing RGD, with the presence of interleukin-4, integrin α2β1 may cause the polarization of macrophages to M2 through STAT6 and to M1 through IRF5 (Cha et al, 2017).…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…Class I myosins have been involved in the regulation of adhesion, motility and the recycling of receptors through the transport of vesicles and by the interaction with different cytoskeletal proteins (Piedra-Quintero et al, 2019, López-Ortega and Santos-Argumedo, 2017, Maravillas-Montero et al, 2011). However, few works are analyzing how class I myosins participate in the signaling mechanism of in leukocytes during cell migration (Salvermoser et al, 2018, López-Ortega et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been reported that MYO1F is induced in colonic macrophages and positively influences αVβ3-integrin accumulation [37]. This process enhances intercellular adhesion between macrophages and stimulates a proinflammatory (M1) phenotype by inducing integrin-linked kinase (ILK)/Protein Kinase B (AKT)/ (mammalian Target of Rapamycin (mTOR) signaling, which, in turn, induces Signal transducers and activators of transcription(STATS), STAT1 and STAT3 activation.…”
Section: Myo1e and Myo1f In Macrophagesmentioning
confidence: 99%
“…Consequently, macrophages lacking MYO1F show reduced intercellular association via integrin-β3 and do not commit to the M1 phenotype. Furthermore, MYO1F upregulation leads to enhanced secretion and production of interleukin-1β and, accordingly, lack of MYO1F has been shown to result in reduced inflammation in a colitis model [37].…”
Section: Myo1e and Myo1f In Macrophagesmentioning
confidence: 99%